Oral vaccination with recombinant Lactobacillus casei expressing Aeromonas hydrophila Aha1 against A. hydrophila infections in common carps. Issue 1 (31st December 2022) - Zhao, Zelin; Wang, Hong; Zhang, Dongxing; Guan, Yongchao; Siddiqui, Shahrood Ahmad; Feng-Shan, Xiao; Cong, Bo
ABSTRACT: The immunogenicity of Aha1, an OMP of Aeromonas hydrophila mediating the adhesion of bacteria onto the mucosal surface of hosts has been established. In this study, recombinant vectors, pPG1 and pPG2, carrying a 1366 bp DNA fragment that was responsible for encoding the 49 kDa Aha1 from A. hydrophila were constructed, respectively, then electroporated into a probiotic strain Lactobacillus casei CC16 separately to generate two types of recombinants, L. casei- pPG1-Aha1 (Lc-pPG1-Aha1) and L. casei -pPG2-Aha1 (Lc-pPG2-Aha1). Subsequently, these were orally administered into common carps to examine their immunogenicity. The expression and localization of the expressed Aha1 protein relative to the carrier L. casei was validated via Western blotting, flow cytometry, and immune fluorescence separately. The recombinant vaccines produced were shown high efficacies, stimulated higher level of antibodies and AKP, ACP, SOD, LZM, C3, C4 in serum in hosts. Immune-related gene expressions of cytokines including IL-10, IL-1β, TNF-α, IFN-γ in the livers, spleens, HK, and intestines were up-regulated significantly. Besides, a more potent phagocytosis response was observed in immunized fish, and higher survival rates were presented in common carps immunized with Lc-pPG1-Aha1 (60%) and Lc-pPG2-Aha1 (50%) after re-infection with virulent strain A. hydrophila . Moreover, the recombinant L. casei were shown a stronger propensity for survivability in the intestine in immunized fish. Taken together, the recombinant L. casei strains might be promising candidates for oral vaccination against A. hydrophila infections in common carps.